Basic Industry Strategy and Orientation Strategy - Zulfa, Bakhitah; Yasin, Muhammad (Journal International Dakwah and Communication, 2022)
This study aims to analyze the portrait of Indonesian agriculture, especially in the development of secondary crops. The method used is a literature study and interviews with agricultural experts in Indonesia. The results of the analysis show that palawija plants have the potential to be further developed in Indonesia. However, the challenges faced in developing palawija crops in Indonesia are climate change which affects rainfall and seasonal patterns, limited land available for cultivation, and low productivity. One solution that can be taken is to develop palawija varieties that are more resistant to climate change and more productive. In addition, the use of modern technology such as drip irrigation, the proper use of fertilizers and pesticides, and good land management can increase the productivity of crops. The conclusion from this analysis is that the development of palawija crops in Indonesia still has great potential, but must be accompanied by efforts to develop technology and good management to increase productivity and overcome the challenges faced.